PENGARUH KEPRIBADIAN DAN KECEMASAN AKAN SEMPITNYA LAPANGAN PEKERJAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA - Fitriani, Dyah (Jurnal Analisis Bisnis Ekonomi, 2010)
This research analyzed about personality, worryness in getting job and entrepreneurial intentions. This research also analyzed the differences between students in personality, worryness in getting job and entrepreneurial intentions. The research's population are Economics Facilty's student in Ahmad Dahlan University. The research sample are student who studied entrepreneurship in Management Programme and Accounting Programme. Sampling technique which is used in this research are purposive sampling. Path analysis and two-way anova analysis are applied to answer the research problem. The conclutions of this research are 1) personality has a significant impact to entrepreneurial intentions and worryness in getting job, 2) worryness in getting job has a significant impact to entrepreneurial intention, and 3) there are no differences among students of Management Programme and Accounting Programme in personality, worryness in getting job and entrepreneurial intentions.